2020
DOI: 10.1101/2020.02.27.968974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential glycosylation of alpha-1-acid glycoprotein (AGP-1) contributes to its functional diversity

Abstract: Alpha-1-acid glycoprotein (AGP-1) is a positive acute phase glycoprotein with uncertain functions. Serum AGP-1 (sAGP-1) is primarily derived from hepatocytes and circulates as 12 to 20 different glycoforms. We isolated a glycoform secreted from stimulated human neutrophils (nAGP-1). Its peptide sequence was identical to hepatocyte-derived sAGP-1, but nAGP-1 differed from sAGP-1 in its chromatographic behaviour, electrophoretic mobility, and glycosylation. The function of these two glycoforms also differed. sAG… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Studies in literature showed that sialoglyco-conjugates are abundant in kidneys, and they could determine SLE organ determinations [ 11 , 12 , 13 , 14 , 15 ]. Seromucoids are released in the early stages of inflammation, act as acute phase reactants, modulate immunity, maintain the barrier function of the capillaries by mediating sphingolipids metabolism [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in literature showed that sialoglyco-conjugates are abundant in kidneys, and they could determine SLE organ determinations [ 11 , 12 , 13 , 14 , 15 ]. Seromucoids are released in the early stages of inflammation, act as acute phase reactants, modulate immunity, maintain the barrier function of the capillaries by mediating sphingolipids metabolism [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of carbohydrates on cells surface are associated with malignant transformation, microbiome status, viral infections, altered immune response [ 1 , 7 , 8 , 9 , 10 ]. Circulant glyco-proteins (orosomucoids or alpha-1-acid glycoprotein) have important functions in immune and inflammatory response and could play a primary role in SLE disease activity and relapse [ 11 , 12 ]. Glycosphingolipids are involved in autoimmune diseases pathogenesis and renal disfunctions [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many AGP isoforms or proteoforms of which about 10–20 glycoforms are detected in the serum. The variations of the AGP glycoforms are of interest to the study of the binding alteration of this protein with certain drugs, and of their usefulness as diagnostic biomarkers for some systemic inflammatory diseases [ 127 , 128 , 129 ]. The quantification of the immunoreactive exorphins derived from milk beta casein A1, casomorphins 5 and 7, is important as these exorphins are potential modulators of numerous regulatory processes in the body as well as potential biomarkers of several diseases.…”
Section: Immunoaffinity Capillary Electrophoresis Applicationsmentioning
confidence: 99%
“…AGP-1 is often considered as one of the inflammatory biomarkers and its functions are not very well understood 3,5,6 . Although hepatocytes are the primary site of synthesis of AGP-1, extra hepatic cells like neutrophils, epithelial cells, monocytes and lymphocytes are known to secrete AGP-1 6,5,7 . However, AGP-1 demonstrates opposing effects on the isolated cells of the innate immune system, although its receptor is yet to be defined 8,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Although hepatocytes are the primary site of synthesis of AGP-1, extra hepatic cells like neutrophils, epithelial cells, monocytes and lymphocytes are known to secrete AGP-1 6,5,7 . However, AGP-1 demonstrates opposing effects on the isolated cells of the innate immune system, although its receptor is yet to be defined 8,7 . Hence we need to understand how AGP-1 modulates the effects of PAF, for which receptor is well characterized on neutrophils.…”
Section: Introductionmentioning
confidence: 99%